2011
DOI: 10.1007/s10290-011-0106-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the duration of EU imports

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 39 publications
7
106
1
1
Order By: Relevance
“…Interestingly, if we increase the level of aggregation so that we consider products defined at the 6-digit or even 4-digit levels, the same pattern remains: almost all spells are very short-lived. This finding, which corresponds to similar findings using country-level data in, for instance, Hess and Persson (2011), suggests that the observed short durations are not some data artefact but indeed capture a relevant economic phenomenon.…”
Section: Datasupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, if we increase the level of aggregation so that we consider products defined at the 6-digit or even 4-digit levels, the same pattern remains: almost all spells are very short-lived. This finding, which corresponds to similar findings using country-level data in, for instance, Hess and Persson (2011), suggests that the observed short durations are not some data artefact but indeed capture a relevant economic phenomenon.…”
Section: Datasupporting
confidence: 88%
“…Prusa, 2011, Hess andPersson 2011), since changed market variables reflect changes in the expected pay-offs of export activity. We include the GDP of each export destination since it will influence the expected revenue of that market through increased competition on a larger market as well as through a greater export opportunity (this ambiguity is discussed in Melitz and Ottaviano, 2008).…”
Section: Market Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative advantage is taken as the opportunity cost a country foregoes in producing a specific commodity as opposed to another country even though it possess absolute advantage in all lines of production. The theory 13 Refer to studies such as Besedes et al, ( (2011) ; Hess et al, (2011Hess et al, ( ,2012and Arawomo (2015). 14 This includes theories from Smith's Absolute Advantage to Ricardo's Comparative Advantage and the HecksherOhlin theory to the New Trade Theory 15 Absolute disadvantage is when a country finds it costly to produce a product with the available level of labour of factor endowment 16 (Heckscher-Ohlin) states that a country will export a commodity which it is more endowed in and import that which it is less endowed in.…”
Section: Traditional Theories Of Tradementioning
confidence: 99%
“…This benchmark study generated a great deal of interest among researchers and results in other countries have confirmed that trade is indeed short-lived (all medians), 2 years in Germany (Nitsch, 2009), 1-2 years for 46 developing countries (Besedeš and Prusa, 2011) and only about 20% of Kenyan exports survive past the first year (Kinuthia, 2014). Subsequently, (Hess and Persson, 2011) found the median import duration in the U.S between 1962 and 2006 to be 1 year.…”
Section: Introductionmentioning
confidence: 99%